TEACHING OF COMMUNICATION SKILLS THROUGH LEARNERS’ CENTERED APPROACH - Awan, Afifa (PEOPLE: International Journal of Social Sciences, 2018)
This research aims to explore how latest methodologies of language teaching bring a positive change in classroom environment by involving students unconsciously in learning process, hence improving their communication skills. One hundred and fifty Undergraduate Students from Bahria University participated in this research. The participants filled a questionnaire about different techniques which were used throughout semester to teach them communication Skills. The data was analyzed in SPSS where Univariate (frequency distribution) and bivariate (Chi-Square test) were applied. Results show that they were able to improve their skills clearly. This research recommends educators to lessen Teachers’ Talking Time and increase Students’ Talking Time. Also use of Concept Checking Questions and Instructions Checking Questionss is encouraged to bring a difference in language learning classrooms. Furthermore, the study suggests that there is a great need to train and motivate learners through different strategies which involve role-play, movie-watch, use of jazz chants, songs and grammatical games.